Positive electrode active material and lithium secondary battery using the same

By forming the lithium ion diffusion path to direct specific crystal planes in lithium composite oxides, the lithium secondary battery achieves enhanced electrochemical properties and stability, addressing the structural instability issues in high-Ni-type materials.

JP7667830B2Active Publication Date: 2025-04-23ECOPRO BM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023158128
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2023-09-22
Publication Date
2025-04-23
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face challenges with high-Ni-type positive electrode active materials, which exhibit high capacity but suffer from structural instability due to Li/Ni cation mixing, leading to rapid deterioration at various temperatures.

Method used

The lithium ion diffusion path in the lithium composite oxide is formed to direct specific crystal planes, such as the (012), (101), and (104) planes, improving the growth of these crystal planes and enhancing the electrochemical properties and stability of the positive electrode active material.

Benefits of technology

This approach maintains high electrochemical properties while eliminating low structural stability, resulting in improved performance and longevity of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667830000007
    Figure 0007667830000007
  • Figure 0007667830000008
    Figure 0007667830000008
  • Figure 0007667830000009
    Figure 0007667830000009
Patent Text Reader

Abstract

To provide a positive electrode active material for an existing lithium secondary battery, in particular, a positive electrode active material that can maintain the high electrochemical properties of a high-Ni type positive electrode active material and eliminate the low structural stability.SOLUTION: A positive electrode active material includes a layered lithium composite oxide capable of lithium intercalation / deintercalation, and the ratio of the peak intensities attributed to the (003) plane and the (012) plane obtained from X-ray diffraction analysis using Cu-Kα rays for the lithium composite oxide satisfies the following formula 1. 0.131≤I(012) / I(003)≤0.143.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material having improved electrochemical properties and stability, in which a lithium ion diffusion path in a lithium composite oxide constituting a positive electrode active material is formed to face a specific crystal plane and the growth of the crystal plane along which the lithium ion diffusion path faces is improved, and to a lithium secondary battery using the positive electrode active material. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as the positive electrode active material of lithium secondary batteries, and examples of such composite oxides that have been researched include LiCoO2, LiMn2O4, LiNiO2, and LiMnO2.

[0005] Among the positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and thus has limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature properties. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems in rate characteristics.

[0007] In addition, a large amount of Li by-products are generated depending on the degree of cation mixing, and most of these Li by-products consist of compounds of LiOH and Li2CO3, which cause gelation during the manufacture of the positive electrode paste and gas generation with the progress of charge and discharge after the electrode is manufactured. Residual Li2CO3 not only increases the swelling phenomenon of the cell, reducing the cycle, but also causes the battery to swell.

[0008] To make up for these shortcomings, the demand for high-Ni type positive electrode active materials with Ni content of 50% or more as positive electrode active materials for secondary batteries has increased. However, while such high-Ni type positive electrode active materials exhibit high capacity characteristics, they have the problem of structural instability due to Li / Ni cation mixing caused by the increased Ni content in the positive electrode active material. Due to the structural instability of such positive electrode active materials, lithium secondary batteries can rapidly deteriorate not only at high temperatures but also at room temperature.

[0009] Meanwhile, in recent years, not only positive electrode active materials containing lithium composite oxides with polycrystalline structures but also positive electrode active materials containing lithium composite oxides with single crystal structures have been proposed (Journal of the Electrochemical Society, Volume 164, Number 7, A1534-A1544 (published date 2017.05.23)).

[0010] The above-mentioned literature describes a lithium composite oxide (LiNi 0.5 Mn 0.3 Co0.2 O2) has disclosed that the stability has been partially improved compared to a lithium composite oxide having a polycrystalline structure with the same composition.

[0011] However, if the calcination temperature is excessively increased or the calcination time is excessively extended in order to form a single crystal of the lithium composite oxide constituting the positive electrode active material, the above-mentioned cation mixing phenomenon may increase.

[0012] In particular, when the cation mixing phenomenon increases in a lithium composite oxide having a single crystal structure, an excessive amount of lithium composite oxide having a semi-safe phase or a rock-salt phase is formed in addition to the originally intended layered structure, and an excessive amount of lithium composite oxide having a phase other than the layered structure is present, which may cause deterioration of the positive electrode active material, which is an aggregate of these. Such deterioration of the positive electrode active material acts as a cause of a decrease in capacity and a shortened lifespan.

[0013] Therefore, there is a clear limit to providing a positive electrode active material with a single crystal structure by simply increasing the sintering temperature of the lithium composite oxide that constitutes the positive electrode active material. Summary of the Invention [Problem to be solved by the invention]

[0014] In a positive electrode active material for a lithium secondary battery, a certain trade-off relationship may be established between some indicators indicating the electrochemical properties of the positive electrode active material and some indicators indicating the stability of the positive electrode active material. Therefore, if the capacity characteristics of the positive electrode active material are excessively improved, the structural stability of the particles constituting the positive electrode active material may be reduced, and the positive electrode active material may not be able to exhibit stable charge and discharge performance.

[0015] Therefore, an object of the present invention is to provide a positive electrode active material that can maintain the high electrochemical properties of existing positive electrode active materials for lithium secondary batteries, in particular, high-Ni type positive electrode active materials, while eliminating the low structural stability.

[0016] Another object of the present invention is to provide a positive electrode active material having improved electrochemical properties and stability, by forming a lithium ion diffusion path in a lithium composite oxide constituting the positive electrode active material so as to direct toward a specific crystal plane and improving the growth of the crystal plane along which the lithium ion diffusion path directs.

[0017] It is yet another object of the present invention to provide a lithium secondary battery using the positive electrode active material defined herein.

[0018] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood from the embodiments of the present invention. Also, it will be easily understood that the object and advantages of the present invention can be realized by the means and combinations thereof described in the claims. [Means for solving the problem]

[0019] According to one aspect of the present invention, there is provided a positive electrode active material which includes a lithium composite oxide having a layered structure capable of lithium intercalation / deintercalation, and in which the ratio of peak intensities attributable to the (003) plane and the (012) plane obtained by X-ray diffraction analysis of the lithium composite oxide using Cu-Kα radiation satisfies the following formula 1: (Formula 1) 0.131≦I(012) / I(003)≦0.143

[0020] The lithium composite oxide may have a shape having a long and short axis, and in this case, the lithium ion diffusion path formed in the lithium composite oxide may be formed so as to be parallel to the long axis direction of the lithium composite oxide.

[0021] Furthermore, the lithium ion diffusion paths formed in the lithium composite oxide are parallel to the (003) plane, but the lithium ion diffusion paths formed in the lithium composite oxide are oriented toward at least one crystal plane selected from the (012) plane, the (101) plane, and the (104) plane. This makes it possible to improve the lithium ion diffusing ability of the lithium composite oxide and the electrochemical characteristics of the positive electrode active material containing the lithium composite oxide.

[0022] Here, the lithium composite oxide is represented by the following formula 1. (chemical 1) Li a Ni 1-(b+c+d+e) Co b M1 c M2 d M3 e O f (Here, M1 is at least one selected from Mn and Al, M2 and M3 are each independently selected from Al, Ba, B, Ce, Cr, Mg, Mn, Mo, Na, K, P, Sr, Ti, W, Nb, and Zr, M1 to M3 are different from each other, and 0.90≦a≦1.15, 0≦b≦0.20, 0≦c≦0.10, 0≦d≦0.05, 0≦e≦0.05, and 1.0≦f≦2.0.)

[0023] In one embodiment, the lithium composite oxide includes at least one primary particle, and for a primary particle on a virtual line crossing a center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide, a density of crystal grain boundaries calculated by the following Equation 5 may be 0.50 or less. (Formula 5) Grain boundary density = (number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line) In this case, the lithium composite oxide may have a single crystal structure.

[0024] In another embodiment, the positive electrode active material is an aggregate of a plurality of lithium composite oxides each including at least one primary particle, and in a cross-sectional SEM image of the lithium composite oxide, the proportion of lithium composite oxides in which the grain boundary density is 0.50 or less, calculated by the following formula 5, with respect to primary particles on a virtual line crossing a center of the lithium composite oxide, among the aggregate, is 30% or more. (Formula 5) Grain boundary density = (number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line)

[0025] According to another aspect of the present invention, there is provided a positive electrode active material including a lithium composite oxide having a layered structure capable of lithium intercalation / deintercalation, the lithium composite oxide including at least one primary particle, the density of crystal grain boundaries calculated by the following formula 5 for a primary particle on a virtual line crossing the center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide being 0.50 or less, (Formula 5) Grain boundary density = (number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line) There is provided a positive electrode active material in which the lithium ion diffusion path formed in the lithium composite oxide is formed so as to be oriented toward at least one crystal plane selected from the (012) plane, the (101) plane, and the (104) plane.

[0026] According to yet another aspect of the present invention, there is provided a positive electrode active material including a lithium composite oxide having a layered structure capable of lithium intercalation / deintercalation, the positive electrode active material being an aggregate of a plurality of lithium composite oxides each consisting of at least one primary particle, in which, in a cross-sectional SEM image of the lithium composite oxide, the proportion of lithium composite oxides in the aggregate having a crystal grain boundary density of 0.50 or less, calculated by the following formula 5, relative to primary particles on a virtual line crossing a center of the lithium composite oxide is 30% or more, (Formula 5) Grain boundary density = (number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line) There is provided a positive electrode active material in which the lithium ion diffusion path formed in the lithium composite oxide is formed so as to be oriented toward at least one crystal plane selected from the (012) plane, the (101) plane, and the (104) plane.

[0027] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the positive electrode active material defined herein. Effect of the Invention

[0028] According to the present invention, the lithium ion diffusion path in the lithium composite oxide constituting the positive electrode active material for a lithium secondary battery is formed so as to be oriented toward a crystal plane through which the diffusion of lithium ions is relatively free, instead of being oriented toward a crystal plane through which the diffusion of lithium ions is blocked. This is expected to improve the electrochemical properties of the positive electrode active material containing the lithium composite oxide.

[0029] Furthermore, by intentionally increasing the growth of a crystal face in which the lithium ions diffuse relatively freely among the crystal faces in the lithium composite oxide, the diffusion ability of the lithium ions through the lithium composite oxide can be improved.

[0030] On the other hand, as described in Journal of the Electrochemical Society, Volume 164, Number 7, A1534-A1544, in order to uniformly crystallize a lithium composite oxide constituting a positive electrode active material for a lithium secondary battery, it is generally necessary to perform firing under relatively severe conditions.

[0031] The lithium composite oxide thus produced having a single crystal structure or a structure close to a single crystal structure (e.g., the number of primary particles constituting the secondary particles is reduced) has a reduced specific surface area compared to that of a lithium composite oxide having a polycrystalline structure, and therefore may have improved stability.

[0032] However, under severe firing conditions, the cation mixing phenomenon may increase, which may cause phase transformation of the lithium composite oxide, resulting in the formation of an excess amount of lithium composite oxide having a quasi-safe phase or rock-salt phase in addition to the intended layered structure. In this way, the coexistence of an excess amount of lithium composite oxide having a phase other than the layered structure with the lithium composite oxide having the layered structure may cause deterioration of the positive electrode active material.

[0033] As a result, in the present invention, the lithium ion diffusion path in the lithium composite oxide constituting the positive electrode active material is formed so as to be oriented toward a specific crystal plane, and the growth of the crystal plane along which the lithium ion diffusion path is oriented is improved, so that it is possible to impart sufficient electrochemical properties and stability to the lithium composite oxide simply by single crystallization, which is performed under relatively less severe firing conditions.

[0034] In addition to the above-mentioned advantages, specific advantages of the present invention will be described below while explaining specific matters for carrying out the invention. [Brief description of the drawings]

[0035] [Figure 1] 1 and 2 are schematic diagrams each showing a cross-sectional image of a lithium composite oxide contained in a positive electrode active material according to various embodiments of the present invention. [Diagram 2] 1 and 2 are schematic diagrams each showing a cross-sectional image of a lithium composite oxide contained in a positive electrode active material according to various embodiments of the present invention. [Diagram 3] 3 to 6 are TEM images of the lithium composite oxides contained in the positive electrode active materials according to Examples 1, 2, 3, and 5 of the present invention, and the TEM images show lithium ion diffusion paths in the lithium composite oxides. [Figure 4]3 to 6 are TEM images of the lithium composite oxides contained in the positive electrode active materials according to Examples 1, 2, 3, and 5 of the present invention, and the TEM images show lithium ion diffusion paths in the lithium composite oxides. [Diagram 5] 3 to 6 are TEM images of the lithium composite oxides contained in the positive electrode active materials according to Examples 1, 2, 3, and 5 of the present invention, and the TEM images show lithium ion diffusion paths in the lithium composite oxides. [Figure 6] 3 to 6 are TEM images of the lithium composite oxides contained in the positive electrode active materials according to Examples 1, 2, 3, and 5 of the present invention, and the TEM images show lithium ion diffusion paths in the lithium composite oxides. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.

[0037] Explanation of terms The term "lithium composite oxide" used in the present application refers to an oxide having a layered structure capable of intercalating / deintercalating lithium (lithium ions), and a composite oxide containing lithium and a metal element. In particular, the lithium composite oxide used in the present application refers to a lithium-nickel-based composite oxide containing lithium and nickel. In addition, the lithium composite oxide used in the present application is an oxide particle constituting a positive electrode active material, and may be a single crystal particle (i.e., a single particle form) or a polycrystalline particle (i.e., a form in which a plurality of particles are aggregated).

[0038] The term "single crystal" used in the present application means a crystal in a state in which there are no grains or grain boundaries within the particle. The term "primary particle" used in the present application means a particle that exists alone without forming an aggregate, or a primary particle that constitutes a secondary particle formed by the aggregate of a plurality of primary particles. The term "lithium composite oxide having a single crystal structure" means a particle in a state in which the primary particle made of the lithium composite oxide is composed of a plurality of crystal grains, or the primary particle does not contain a grain boundary.

[0039] The term "secondary particle" used in this application means a primary particle itself which is the above-mentioned lithium composite oxide, or a particle formed by agglomeration of at least two primary particles. In this case, a secondary particle consisting of a single primary particle and / or a secondary particle formed by agglomeration of at least two primary particles may coexist in the positive electrode active material. When at least two primary particles are agglomerated to form a secondary particle, a crystal grain boundary or grain boundary surface formed at the interface between the two primary particles is present in the secondary particle.

[0040] The term "grain boundary density" as used in this application means the number of grain boundaries or grain boundary surfaces formed by the presence of at least two primary particles within a secondary particle; the greater the number of primary particles present within a secondary particle, the greater the density of the grain boundaries, and the smaller the number of primary particles present within a secondary particle, the smaller the density of the grain boundaries.

[0041] In the present application, the density of crystal grain boundaries may be calculated based on the number of primary particles on a virtual line that crosses the center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide, using the following formula 5. In this case, the direction of the line may be a direction crossing the center of the lithium composite oxide in the short axis direction. (Formula 5) Grain boundary density = (number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line)

[0042] If the number of primary particles present within the secondary particle is one, the grain boundary density calculated by the above formula is 0, and if the number of primary particles present within the secondary particle is three or more, the grain boundary density calculated by the above formula exceeds 0.5.

[0043] Meanwhile, in the present application, the secondary particle may be a particle consisting of a single primary particle having a single crystal structure, but is not necessarily limited thereto. That is, in the present application, the secondary particle may be understood as a particle consisting of a single single crystal particle, or a particle formed by agglomeration of at least two single crystal particles. The definition of such a secondary particle may be more clearly explained by the definition of the positive electrode active material described later.

[0044] The term "positive electrode active material" used in the present application is a broad concept including the above-mentioned secondary particles, and while a single secondary particle itself may be a positive electrode active material, in the present application, an aggregate of multiple secondary particles having the same and / or different crystal boundary densities may be defined as a positive electrode active material.

[0045] Therefore, in the definition of the positive electrode active material described later, the description of the secondary particles having the characteristics of an aggregate of a plurality of secondary particles, the description of the secondary particles constituting the positive electrode active material, and the description of the primary particles constituting the secondary particles need to be understood separately.

[0046] Hereinafter, a positive electrode active material according to the present invention and a lithium secondary battery using a positive electrode including the positive electrode active material will be described in more detail.

[0047] positive electrode active material According to one aspect of the present invention, there is provided a positive electrode active material including a lithium composite oxide having a layered structure capable of lithium intercalation / deintercalation.

[0048] The lithium composite oxide may include at least one primary particle, and if the lithium composite oxide includes a plurality of primary particles, the plurality of primary particles may exist as secondary particles that are aggregates of each other. On the other hand, if the lithium composite oxide includes a single primary particle, the lithium composite oxide is called a lithium composite oxide having a single-crystal structure.

[0049] The primary particle means one crystal grain or crystallite, and the secondary particle means an aggregate formed by the aggregation of a plurality of primary particles. The primary particle may be rod-shaped, elliptical, and / or circular, or may be irregular.

[0050] A gap and / or a grain boundary may exist between the primary particles constituting the secondary particle. For example, the primary particles may be separated from adjacent primary particles inside the secondary particle to form an internal gap. Also, the primary particles may contact adjacent primary particles to form an internal gap without forming a grain boundary, thereby forming a surface present within the secondary particle.

[0051] On the other hand, the surface of the primary particles present on the outermost surface of the secondary particles, which is exposed to the outside air, forms the surface of the secondary particles.

[0052] Here, the average particle size of the primary particles is within a range of 0.1 μm to 10 μm, preferably 1.0 μm to 10 μm, so that the optimal density of the positive electrode manufactured using the positive electrode active material according to various embodiments of the present invention can be realized. Also, the average particle size of the secondary particles may be 3 μm to 20 μm, depending on the number of aggregated primary particles.

[0053] Meanwhile, the positive electrode active material according to the present invention may be defined as an aggregate of a plurality of secondary particles having the same and / or different grain boundary densities.

[0054] The density of the crystal grain boundaries may be calculated based on the number of primary particles P on a virtual straight line L that crosses the center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide, using the following formula 5. (Formula 5) Grain boundary density = (number of boundaries (B) between primary particles on the virtual line (L) / number of primary particles (P) on the virtual line (L))

[0055] For example, the density of the crystal grain boundaries of the lithium composite oxide calculated with reference to FIGS. 1 and 2, which are schematic diagrams illustrating cross-sectional images of the lithium composite oxide included in the positive electrode active materials according to various embodiments of the present invention, is shown in Table 1 below. [Table 1]

[0056] When the grain boundary density represented by Formula 5 has a value of 0.90 or less, the surface area and grain boundary surface of the lithium composite oxide can be reduced, thereby reducing the possibility of a side reaction between the positive electrode active material and an electrolyte, and improving not only the high temperature stability but also the storage stability of the positive electrode active material.

[0057] Meanwhile, according to one embodiment of the present invention, the proportion of lithium composite oxide in which the grain boundary density calculated by Equation 5 is 0.50 or less with respect to primary particles on a virtual line crossing the center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide among the aggregates of secondary particles may be 30% or more.

[0058] The surface area of ​​the lithium composite oxide contained in the positive electrode active material and the grain boundaries defined by the primary particles constituting the lithium composite oxide are regions where side reactions may occur at the interface and between the positive electrode active material and the electrolyte and the surface. Here, as shown in Figures 1 and 2, the grain boundaries defined by the primary particles present in the lithium composite oxide may be understood as, for example, the interface between two adjacent primary particles.

[0059] In this case, by reducing the surface area of ​​the lithium composite oxide and the grain boundary surface defined by the primary particles in the lithium composite oxide, it is possible to improve the thermal stability of the positive electrode active material and prevent or mitigate problems caused by the instability of the positive electrode active material (e.g., reduced storage stability such as gas generation due to a side reaction with the electrolyte).

[0060] As a result, by making the ratio of lithium composite oxides having a grain boundary density of 0.50 or less, calculated by the formula 5, in the aggregate of secondary particles 30% or more, it is possible to provide a positive electrode active material that can stably maintain electrochemical characteristics.

[0061] Meanwhile, the proportion of lithium composite oxides having a grain boundary density of 0.50 or less, calculated by Equation 5, among the secondary particle aggregates, can be increased by modifying process conditions in some steps of the lithium composite oxide synthesis process. For example, the proportion of lithium composite oxides having a grain boundary density of 0.50 or less can be increased by adjusting the temperature / time of a primary firing of the precursor of the lithium composite oxide and / or the temperature / time of a secondary firing of the resultant of the primary firing of the precursor.

[0062] However, as the firing conditions of the precursor and / or the lithium composite oxide become relatively severe, a cation mixing phenomenon may increase, and the cation mixing phenomenon may induce phase transformation of the lithium composite oxide.

[0063] Therefore, by making the proportion of lithium composite oxides having a grain boundary density of 0.50 or less, calculated by Equation 5, in the secondary particle aggregate to be 95% or less, preferably 90% or less, and more preferably 80% or less, it is possible to achieve a balance between the lithium composite oxides having a grain boundary density of 0.50 or less and the lithium composite oxides having a grain boundary density of more than 0.50 in the secondary particle aggregate.

[0064] The lithium composite oxide according to an embodiment of the present invention may contain at least Ni and Co. In addition to Ni and Co, the lithium composite oxide may further contain Mn and / or Al, and may further contain a dopant other than the above-mentioned metal elements.

[0065] Specifically, the lithium composite oxide is represented by the following formula 1. (chemical 1) Li a Ni 1-(b+c+d+e) Co b M1 c M2 d M3 e O f (Here, M1 is at least one selected from Mn and Al, M2 and M3 are each independently selected from Al, Ba, B, Ce, Cr, Mg, Mn, Mo, Na, K, P, Sr, Ti, W, Nb, and Zr, M1 to M3 are different from each other, and 0.90≦a≦1.15, 0≦b≦0.20, 0≦c≦0.10, 0≦d≦0.05, 0≦e≦0.05, and 1.0≦f≦2.0.)

[0066] On the other hand, the lithium composite oxide may be a high-Ni type lithium composite oxide in which the molar ratio of nickel calculated by the following formula 4 is 0.6 or more, preferably 0.7, and more preferably 0.8 or more, among the lithium composite oxides represented by Chemical Formula 1. (Formula 4) Ni(molar ratio)=Ni(mol%) / (Ni(mol%)+Co(mol%)+M1(mol%)+M2(mol%)+M3(mol%))

[0067] As mentioned above, high-Ni type lithium composite oxides have the advantage of having relatively high electrochemical properties compared to lithium composite oxides with low Ni content, but they have the problem of structural instability due to Li / Ni cation mixing caused by the increase in Ni content of the lithium composite oxide. Due to such structural instability of the positive electrode active material, lithium secondary batteries can rapidly deteriorate not only at high temperatures but also at room temperature.

[0068] However, even if the lithium composite oxide according to the present invention has a high-Ni type composition, it is possible to improve the electrochemical properties of the lithium composite oxide and prevent a decrease in stability by controlling the properties of the crystal plane or exposed surface described later.

[0069] Specifically, the lithium ion diffusion paths formed in the lithium composite oxide are formed to be parallel to the major axis direction of the lithium composite oxide, thereby improving the diffusibility of the lithium ions through the lithium composite oxide.

[0070] Here, the lithium ion diffusion path refers to a main one-dimensional and / or two-dimensional path through which lithium ions are transported / diffused in the lithium composite oxide by a vacancy hopping mechanism.

[0071] In addition, the lithium ion diffusion path is preferably formed so as to be parallel to the (003) plane confirmed by X-ray diffraction analysis using Cu-Kα radiation for the lithium composite oxide. If the lithium ion diffusion path in the lithium composite oxide is formed so as to be oriented toward the (003) plane, the diffusion of the lithium ions may be blocked by the (003) plane, and the diffusibility of the lithium ions through the lithium composite oxide may be reduced.

[0072] On the other hand, the lithium ion diffusion path is formed so as to be oriented toward at least one crystal plane selected from the (012) plane, the (101) plane, and the (104) plane, in which the lithium ions diffuse relatively freely, relative to the (003) plane, whereby the diffusibility of the lithium ions through the lithium composite oxide can be improved.

[0073] That is, according to the present invention, the lithium ion diffusion path in the lithium composite oxide constituting the positive electrode active material for a lithium secondary battery is formed so as to be oriented toward a crystal plane through which the diffusion of lithium ions is relatively free, instead of being oriented toward a crystal plane through which the diffusion of lithium ions is blocked. This is expected to improve the electrochemical properties of the positive electrode active material containing the lithium composite oxide.

[0074] In this case, the lithium ion diffusion path is oriented toward a specific crystal plane, which means that the angle between the direction perpendicular to the specific crystal plane and the direction of the lithium ion diffusion path is 90 degrees or less, preferably 60 degrees or less, and more preferably 45 degrees or less.

[0075] Furthermore, according to the present invention, the growth of the crystal plane along which the lithium ion diffusion path is directed can be improved by adding flux to a mixture of the hydroxide precursor and lithium raw material (e.g., LiOH, etc.) before primary calcination to obtain the lithium composite oxide by heat treatment of the hydroxide precursor of the lithium composite oxide, and then heat treatment. In particular, the growth of the crystal plane along which the lithium ion diffusion path is relatively free can be further improved compared to the crystal plane along which the lithium ion diffusion is blocked, by adding flux to a mixture of the hydroxide precursor and lithium raw material (e.g., LiOH, etc.) before primary calcination, and then heat treatment.

[0076] Fluxes used to improve the growth of crystal faces where lithium ions are relatively free to diffuse may include, for example, alkali metal compounds (hydroxides, chlorides, nitrides, carbonates, sulfates, etc.) such as NaOH, KCl, NaNO3, or chlorides such as NH4Cl.

[0077] On the other hand, the ratio of peak intensities attributable to the (003) plane and the (012) plane obtained by X-ray diffraction analysis using Cu-Kα radiation for the lithium composite oxide can satisfy the following formula 1. (Formula 1) 0.131≦I(012) / I(003)≦0.143

[0078] When I(012) / I(003) calculated by the above formula 1 is less than 0.131, the growth of the (012) plane, in which lithium ions diffuse relatively freely compared to the (003) plane in which the diffusion of lithium ions is blocked, is insufficient, and the effect of improving the electrochemical properties of the lithium composite oxide associated with the growth of the crystal plane along which the lithium ion diffusion path is directed becomes insignificant.

[0079] On the other hand, when I(012) / I(003) calculated by the above formula 1 exceeds 0.143, the growth of the (012) plane formed along the length direction of the lithium ion diffusion path becomes excessively large, which may result in a decrease in the diffusibility of the lithium ions through the lithium composite oxide or a decrease in the stability of the crystal structure of the lithium composite oxide.

[0080] Furthermore, the ratio of peak intensities attributable to the (003) plane and the (104) plane obtained by X-ray diffraction analysis using Cu-Kα radiation on the lithium composite oxide can satisfy the following formula 2. (Formula 2) 0.630≦I(104) / I(003)≦0.698

[0081] Similarly, when I(104) / I(003) calculated by the above formula 2 is less than 0.630, the growth of the (104) plane, in which lithium ions diffuse relatively freely compared to the (003) plane in which the diffusion of lithium ions is blocked, is insufficient, and the effect of improving the electrochemical properties of the lithium composite oxide associated with the growth of the crystal plane along which the lithium ion diffusion path is directed is negligible.

[0082] On the other hand, when I(104) / I(003) calculated by Equation 2 exceeds 0.698, the growth of the (104) plane formed along the length direction of the lithium ion diffusion path becomes excessively large, which may decrease the diffusion ability of the lithium ions through the lithium composite oxide or decrease the stability of the crystal structure of the lithium composite oxide.

[0083] Furthermore, the ratio of peak intensities attributable to the (003) plane and the (101) plane obtained by X-ray diffraction analysis using Cu-Kα radiation on the lithium composite oxide can satisfy the following formula 3. (Formula 3) 0.379≦I(101) / I(003)≦0.421

[0084] Similarly, when I(101) / I(003) calculated by the above formula 3 is less than 0.379, the growth of the (101) plane, where lithium ions diffuse relatively freely compared to the (003) plane where the diffusion of lithium ions is blocked, is insufficient, and the effect of improving the electrochemical properties of the lithium composite oxide associated with the growth of the crystal plane along which the lithium ion diffusion path is directed is negligible.

[0085] On the other hand, when I(101) / I(003) calculated by Equation 3 exceeds 0.421, the growth of the (101) plane formed along the length direction of the lithium ion diffusion path becomes excessively large, which may decrease the diffusion ability of the lithium ions through the lithium composite oxide or decrease the stability of the crystal structure of the lithium composite oxide.

[0086] Furthermore, the lithium composite oxide included in the positive electrode active material according to some embodiments of the present invention may include a coating layer that covers at least a portion of the surface of the primary particles (e.g., grain boundaries between the primary particles) and / or secondary particles formed by aggregation of the primary particles.

[0087] For example, the coating layer may be present so as to cover at least a part of the exposed surface of the primary particles, in particular, the coating layer may be present so as to cover at least a part of the exposed surface of the primary particles that are the outermost of the secondary particles.

[0088] Thus, the coating layer may exist as a layer that continuously or discontinuously coats the surfaces of the primary particles and / or the secondary particles formed by agglomeration of the primary particles. When the coating layer exists discontinuously, it may exist in the form of islands.

[0089] The coating layer thus present can contribute to maintaining high electrochemical properties of lithium composite oxides, particularly high-Ni type lithium composite oxides, while resolving low structural stability.

[0090] In addition, the coating layer may exist in the form of a solid solution that does not form a boundary with the primary particles and / or the secondary particles formed by agglomeration of the primary particles.

[0091] The coating layer may contain at least one oxide represented by the following Chemical formula 2. That is, the coating layer can be defined as a region in which the oxide represented by the following Chemical formula 2 is present. (Case 2) Li a A b O c (Here, A is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, and 0≦a≦10, 0≦b≦8, and 2≦c≦15.)

[0092] The coating layer may be in a form in which different oxides are simultaneously present in one layer, or in which the different oxides represented by Chemical Formula 2 are each present in a separate layer.

[0093] The oxide represented by Chemical formula 2 may be in a state of being physically and / or chemically bonded to the primary particles represented by Chemical formula 1. The oxide may also be in a state of forming a solid solution with the primary particles represented by Chemical formula 1.

[0094] The lithium composite oxide according to the present embodiment includes a coating layer that covers at least a portion of the surface of the primary particles (e.g., interfaces between the primary particles) and / or secondary particles formed by agglomeration of the primary particles, thereby enhancing structural stability. In addition, when such a lithium composite oxide is used as a positive electrode active material for a lithium secondary battery, the electrochemical properties and stability of the positive electrode active material can be improved. In addition, the oxide can reduce residual lithium in the lithium composite oxide and act as a pathway for lithium ions to move.

[0095] In some cases, the oxide may be present not only at the interfaces between the primary particles and at least a portion of the surfaces of the secondary particles, but also in internal voids formed inside the secondary particles.

[0096] The oxide is a composite oxide of lithium and an element represented by A, or an oxide of A, and the oxide is, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a B b O c , W b O c , Zr b O c , Ti b O c Or B b O cNon-limiting examples of the oxide include Li2B4O7, Li3BO3, Li2B2O7, Li2BO 13 , Li2VO3, Li3VO4, Li6Zr3O9, Li2ZrO3, Li 5.5 Zr 2.6 2O8, Li 44 Ba 19 , Li4Ba, Li2TiO3, LiTi7O4, and LiTi2O4. The above examples are merely for the convenience of understanding, and the oxides defined in the present application are not limited to the above examples.

[0097] In another embodiment, the oxide may be an oxide of lithium and at least two elements represented by A, or may further include an oxide of lithium and at least two elements represented by A. The oxide of lithium and at least two elements represented by A may be, for example, Li a (W / Ti) b O c , Li a (W / Zr) b O c , Li a (W / Ti / Zr) b O c , Li a (W / Ti / B) b O c It may be, but is not necessarily limited to, the above.

[0098] Here, the oxide may exhibit a concentration gradient that decreases from the surface portion of the secondary particle toward the center portion of the secondary particle, whereby the concentration of the oxide may decrease from the surface portion of the secondary particle toward the center portion of the secondary particle.

[0099] As described above, the oxide exhibits a concentration gradient that decreases from the surface portion of the secondary particle toward the center portion of the secondary particle, and thus the residual lithium present on the surface of the lithium composite oxide can be effectively reduced, and side reactions due to unreacted residual lithium can be prevented. In addition, the oxide can prevent a decrease in crystallinity in the inner surface region of the lithium composite oxide. In addition, the oxide can prevent the overall structure of the lithium composite oxide from collapsing during an electrochemical reaction.

[0100] Furthermore, the coating layer may include a first coating layer including at least one oxide represented by Chemical Formula 2 and a second coating layer including at least one oxide represented by Chemical Formula 2, but different from the oxide included in the first coating layer.

[0101] For example, the first coating layer may be present to cover at least a portion of the exposed surface of the primary particles that are the outermost of the secondary particles, and the second coating layer may be present to cover at least a portion of the exposed surface of the primary particles that is not covered by the first coating layer and the surface of the first coating layer.

[0102] Lithium secondary battery According to yet another aspect of the present invention, a positive electrode may be provided, the positive electrode active material layer including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. Here, the positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, since the positive electrode active material is as described above, detailed description will be omitted for convenience, and only the remaining components not described above will be described below.

[0103] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0104] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0105] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.

[0106] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0107] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0108] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0109] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0110] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0111] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0112] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0113] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0114] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0115] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0116] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0117] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0118] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.

[0119] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0120] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskey such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0121] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0122] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0123] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.

[0124] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0125] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0126] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0127] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0128] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.

[0129] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0130] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0131] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0132] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0133] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0134] Production Example 1. Production of positive electrode active material Example 1 A lithium composite oxide hydroxide precursor, NiCoMn(OH)2 (Ni:Co:Mn=91:8:1 (at%)), was synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. The average particle size (D50) of the lithium composite oxide hydroxide precursor was 3.0 μm.

[0135] Next, LiOH (Li / (Ni+Co+Mn) molar ratio=1.05±0.05) was mixed with the first hydroxide precursor, and then the mixture was heated in a sintering furnace at 770°C at 2°C per minute while maintaining an O2 atmosphere, and heat-treated for 12 hours (primary sintering) to obtain a lithium composite oxide. At this time, before starting the heat treatment, 2.0 mol% of NaNO3 was added based on the total amount of the first hydroxide precursor and LiOH.

[0136] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0137] Finally, the mixture was heated in a sintering furnace at 2°C per minute up to 700°C for 12 hours (secondary sintering) while maintaining an O2 atmosphere, to obtain a positive electrode active material containing a lithium composite oxide.

[0138] Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that 3.0 mol % of NH4Cl was used instead of 2.0 mol % of NaNO3.

[0139] Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that 1.0 mol % of KCl was used instead of 2.0 mol % of NaNO3.

[0140] Example 4 A positive electrode active material was produced in the same manner as in Example 1, except that 3.0 mol % of KCl was used instead of 2.0 mol % of NaNO3.

[0141] Example 5 A positive electrode active material was prepared in the same manner as in Example 1, except that 3.0 mol % of NaOH was used instead of 2.0 mol % of NaNO3.

[0142] Example 6 A positive electrode active material was prepared in the same manner as in Example 1, except that 5.0 mol % NaOH was used instead of 2.0 mol % NaNO3.

[0143] Example 7 A positive electrode active material was prepared in the same manner as in Example 1, except that 3.0 mol % of NaCl was used instead of 2.0 mol % of NaNO3.

[0144] Comparative Example 1 A positive electrode active material was prepared in the same manner as in Example 1, except that NaNO3 was not added before the primary firing.

[0145] Comparative Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that 0.5 mol % of NH4Cl was used instead of 2.0 mol % of NaNO3.

[0146] Comparative Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that 1.0 mol % of NH4Cl was used instead of 2.0 mol % of NaNO3.

[0147] Comparative Example 4 A positive electrode active material was prepared in the same manner as in Example 1, except that 0.5 mol % of KCl was used instead of 2.0 mol % of NaNO3.

[0148] Comparative Example 5 A positive electrode active material was prepared in the same manner as in Example 1, except that 1.0 mol % of NaOH was used instead of 2.0 mol % of NaNO3.

[0149] Comparative Example 6 A positive electrode active material was prepared in the same manner as in Example 1, except that the content of NaNO3 added before the primary firing was 3.0 mol%.

[0150] Comparative Example 7 A positive electrode active material was prepared in the same manner as in Example 1, except that the content of NaNO3 added before the primary firing was 5.0 mol%.

[0151] Comparative Example 8 A positive electrode active material was produced in the same manner as in Example 1, except that 5.0 mol % of NaCl was used instead of 2.0 mol % of NaNO3.

[0152] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 94 wt% of each positive electrode active material prepared in Preparation Example 1, 3 wt% of artificial graphite, and 3 wt% of PVDF binder in 3.5 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was applied to a 20 μm-thick aluminum (Al) thin film as a positive electrode current collector, dried, and roll-pressed to prepare a positive electrode. The loading level of the positive electrode was 7 mg / cm. 2 and the electrode density is 3.2 g / cm 3 It was.

[0153] A lithium foil was used as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separator, and a liquid electrolyte containing LiPF6 at a concentration of 1.15 M in a solvent containing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7 was used to fabricate a coin battery according to a commonly known manufacturing process.

[0154] Experimental Example 1. Structural analysis of positive electrode active material (1) Cross-sectional SEM analysis of positive electrode active material A cross-sectional SEM image of the lithium composite oxide contained in the positive electrode active material prepared in Preparation Example 1 was obtained using FE-SEM (Bruker), and then the proportion of lithium composite oxides having a grain boundary density of 0.50 or less, calculated by the following Equation 5, was calculated from the cross sections of 100 lithium composite oxides captured in the cross-sectional SEM image. (Formula 5) Grain boundary density=(number of boundaries between primary particles on a virtual line that crosses the center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide / number of primary particles on the virtual line)

[0155] The measurement results of the grain boundary density are shown in Table 2 below. [Table 2]

[0156] (2) TEM analysis of positive electrode active material In Preparation Example 1, TEM images were obtained for the lithium composite oxides contained in the positive electrode active materials according to Examples 1, 2, 3, and 5, and then the directionality of the lithium ion diffusion paths formed in the lithium composite oxide was confirmed from the TEM images. In addition, the SAD diffraction pattern was indexed to confirm the crystal planes of the lithium composite oxide along which the lithium ion diffusion paths formed in the lithium composite oxide were oriented. The measurement results are shown in FIGS. 3 to 6.

[0157] 3 to 6, it can be seen that the lithium ion diffusion paths formed in the lithium composite oxides contained in the positive electrode active materials according to Examples 1, 2, 3, and 5 were formed in the same direction as the major axis direction of the lithium composite oxides. In particular, it can be seen that the lithium ion diffusion paths formed in the lithium composite oxides were formed in a direction approximately parallel to the (003) plane.

[0158] It was confirmed that the lithium ion diffusion paths formed in the lithium composite oxide were formed to be oriented toward the (012), (101) and / or (104) planes.

[0159] That is, the lithium ion diffusion paths formed in the lithium composite oxides contained in the respective positive electrode active materials according to Examples 1, 2, 3, and 5 are formed so as to be oriented toward the (012), (101), and / or (104) planes in which lithium ions diffuse relatively freely, instead of being oriented toward the (003) plane in which lithium ion diffusion is blocked. This is expected to improve the electrochemical properties of the positive electrode active materials containing the lithium composite oxides.

[0160] (3) XRD analysis of positive electrode active material X-ray diffraction (XRD) analysis was performed on each of the positive electrode active materials produced in Production Example 1 to detect peaks attributable to the crystal planes of the lithium composite oxide contained in the positive electrode active materials. The XRD analysis was performed using a Bruker D8 Advance diffractometer using Cu-Kα radiation (1.540598 Å), and the intensity ratios between peaks attributable to specific crystal planes are shown in Tables 3 and 4 below. [Table 3] [Table 4]

[0161] Experimental Example 2: Evaluation of the electrochemical properties of lithium secondary batteries The lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 was subjected to a charge-discharge experiment at 25° C., voltage range of 3.0V to 4.3V, and discharge rate of 0.1C to 5.0C using an electrochemical analyzer (Toyo, Toscat-3100) to measure the C-rate efficiency at 5.0C / 0.1C.

[0162] In addition, the same lithium secondary battery was charged / discharged 50 times at 25°C and 1C / 1C within a driving voltage range of 3.0V to 4.4V, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured.

[0163] The measurement results are shown in Table 5 below. [Table 5]

[0164] Referring to the results in Table 5, it can be seen that the lithium secondary batteries manufactured using the positive electrode active materials according to Examples 1 to 7 exhibit superior effects in terms of C-rate efficiency (output characteristics) and cycle capacity retention rate compared to the lithium secondary batteries manufactured using the positive electrode active materials according to Comparative Examples 1 to 8.

[0165] Specifically, in the case of Comparative Example 1, it can be confirmed that the electrochemical properties are inferior to those of Examples 1 to 7 due to the elimination of the intentional growth of the crystal plane along which the lithium ion diffusion path is directed.

[0166] On the other hand, in the case of Comparative Example 7 in which the content of NaNO3 added before the primary firing was 5.0 mol%, the ratio of lithium composite oxides having a grain boundary density of 0.5 or less among all the lithium composite oxides constituting the positive electrode active material was excessively reduced, which is expected to result in deterioration of the electrochemical characteristics compared to Examples 1 to 7.

[0167] In addition, in the case of Comparative Example 8, in which the content of NaCl added before the primary firing was 5.0 mol%, the proportion of lithium composite oxides having a grain boundary density of 0.5 or less among all the lithium composite oxides constituting the positive electrode active material was excessively increased, and it is expected that the electrochemical properties were rather deteriorated compared to Examples 1 to 8.

[0168] Experimental Example 2. Evaluation of the stability of the positive electrode active material In order to measure the weight loss rate of each positive electrode active material prepared in Preparation Example 1, the weight loss rate was measured by heating at a heating rate of 10°C / min up to 810°C under Ar atmosphere at normal pressure using a TGA-MS device. At this time, the measurement sample amount was 65mg to 66mg because the intensity of the MS signal may be changed.

[0169] The weight loss rate of the positive electrode prepared in Preparation Example 2 was also measured in the same manner, and the temperature at which the weight loss peak first appeared was measured.

[0170] The measurement results are shown in Table 6 below. [Table 6]

[0171] Referring to the results in Table 6, it can be seen that the thermal stability of the positive electrode active materials according to Examples 1 to 7 is generally higher than that of the positive electrode active materials according to Comparative Examples 1 to 8. It can be seen that the stability of such a positive electrode active material is intricately related to the proportion of lithium composite oxide having a grain boundary density of 0.5 or less among all the lithium composite oxides constituting the positive electrode active material, and the intentional growth of specific crystal planes of the lithium composite oxide.

[0172] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be said to be within the scope of the claims of the present invention.

Claims

1. A positive electrode active material comprising a layered lithium composite oxide capable of lithium intercalation / deintercalation, The ratio of peak intensities attributable to the (003) plane and the (012) plane obtained by X-ray diffraction analysis of the lithium composite oxide using Cu-Kα radiation satisfies the following formula 1: In the lithium composite oxide, the molar ratio of Ni to all metal elements other than lithium is 0.6 or more; A positive electrode active material, the positive electrode active material having a weight loss rate of 0.91% or less when heated to 810° C. at a heating rate of 10° C. / min in an Ar atmosphere at normal pressure. (Formula 1) 0.131≦I(012) / I(003)≦0.143

2. The positive electrode active material according to claim 1, wherein the ratio of peak intensities attributable to the (003) plane and the (104) plane obtained by X-ray diffraction analysis of the lithium composite oxide using Cu-Kα radiation satisfies the following formula 2. (Formula 2) 0.630≦I(104) / I(003)≦0.698

3. The positive electrode active material according to claim 1, wherein the ratio of peak intensities attributable to the (003) plane and the (101) plane obtained by X-ray diffraction analysis of the lithium composite oxide using Cu-Kα radiation satisfies the following formula 3. (Formula 3) 0.379≦I(101) / I(003)≦0.421

4. The positive electrode active material according to claim 1 , wherein the lithium ion diffusion paths formed in the lithium composite oxide are formed parallel to a major axis direction of the lithium composite oxide.

5. The positive electrode active material according to claim 1 , wherein the lithium ion diffusion paths formed in the lithium composite oxide are parallel to a (003) plane.

6. 2. The positive electrode active material according to claim 1, wherein the lithium ion diffusion path formed in the lithium composite oxide is formed so as to be oriented toward at least one crystal plane selected from a (012) plane, a (101) plane, and a (104) plane.

7. The positive electrode active material according to claim 1 , wherein the lithium composite oxide is represented by the following Chemical Formula 1. (Chem.1) Li a Ni 1-(b+c+d+e) Co b M1 c M2 d M3 e O f (where: M1 is at least one selected from Mn and Al; M2 and M3 are each independently selected from Al, Ba, B, Ce, Cr, Mg, Mn, Mo, Na, K, P, Sr, Ti, W, Nb, and Zr; M1 to M3 are different from each other, 0.90≦a≦1.15, 0≦b≦0.20, 0≦c≦0.10, 0≦d≦0.05, 0≦e≦0.05, 1.0≦f≦2.

0.

8. The positive electrode active material according to claim 7 , wherein the lithium composite oxide represented by Chemical Formula 1 has a molar ratio of nickel calculated by the following Formula 4 of 0.6 or more. (Formula 4) Ni (molar ratio) = Ni (mol%) / (Ni (mol%) + Co (mol%) + M1 (mol%) + M2 (mol%) + M3 (mol%))

9. 2. The positive electrode active material according to claim 1, wherein the lithium composite oxide has an average particle size of 0.1 μm to 20 μm.

10. The lithium composite oxide includes at least one primary particle, 2. The positive electrode active material according to claim 1, wherein in a cross-sectional SEM image of the lithium composite oxide, a grain boundary density calculated by the following formula 5 for primary particles on a virtual line crossing a center of the lithium composite oxide is 0.50 or less: (Formula 5) Grain boundary density=(number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line)

11. the positive electrode active material is an aggregate of a plurality of lithium composite oxides each composed of at least one primary particle, 2. The positive electrode active material according to claim 1, wherein a proportion of lithium composite oxide in the aggregate, in which primary particles on a virtual line crossing a center of the lithium composite oxide in a cross-sectional SEM image of the lithium composite oxide have a grain boundary density of 0.50 or less, calculated by the following formula 5, is 30% or more: (Formula 5) Grain boundary density=(number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line)

12. Further comprising a coating layer covering at least a part of the surface of the lithium composite oxide; The positive electrode active material according to claim 1 , wherein the coating layer comprises at least one oxide represented by the following Chemical Formula 2: (Case 2) Li a A b O c (where: A is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦a≦10, 0≦b≦8, 2≦c≦15.

13. A positive electrode active material comprising a layered lithium composite oxide capable of lithium intercalation / deintercalation, In the lithium composite oxide, the molar ratio of Ni to all metal elements other than lithium is 0.6 or more; The lithium composite oxide includes at least one primary particle, In a cross-sectional SEM image of the lithium composite oxide, a grain boundary density calculated by the following formula 5 for primary particles on a virtual line crossing a center of the lithium composite oxide is 0.50 or less, (Formula 5) Grain boundary density=(number of boundaries between primary particles on the imaginary line / number of primary particles on the imaginary line) the lithium ion diffusion path formed in the lithium composite oxide is formed so as to be oriented toward at least one crystal plane selected from a (012) plane, a (101) plane, and a (104) plane; A positive electrode active material, the positive electrode active material having a weight loss rate of 0.91% or less when heated to 810° C. at a heating rate of 10° C. / min in an Ar atmosphere at normal pressure.

Citation Information

Patent Citations

  • Lithium nickelate as positive electrode active material of lithium secondary battery and manufacture thereof

    JP1997270260A

  • Lithium nickel composite oxide, manufacture thereof, and positive electrode active substance for secondary battery

    JP1998069910A

  • Method for producing lithium composite metal oxide

    JP2012109190A

  • Lithium-nickel-containing composite oxide and nonaqueous electrolyte secondary battery

    JP2017226576A

  • Positive electrode active material for lithium secondary battery and lithium secondary battery containing the same

    JP2017533568A